(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article are considered the issues of training political science specialists in modern terms. The role of political science in the formation of a social responsible citizen is also given. The training of a of new generation specialist depends not only on the quality of the educational programs, but also on the professional level of the professors and their teaching skills, which should facilitate the development of students’ logical thinking, civic engagement, analytical skills and their exploratory approach to the educational material. In modern terms political science should be a core in shaping the social responsibility of a citizen. Keywords: politics, political science, methodology, modernization, political system, political analysis, political stability.